Prevalencia de abuso y factores asociados en una escuela de medicina Colombiana (2011)
Different forms of abusive practices are very common in medical schools and have serious implications on vocational and professional formation. The aim of this study is to determine the prevalence of perception of abuse in a university in Colombia and to identify associated factors. Methods: A cross-sectional study was conducted from September to December 2008 in a private medical school. A proportional cycle-based stratified sampling technique and randomized sampling per semester was done. Socio demographic, academic, and abuse-related variables were obtained. Results: One hundred twenty-eight students participated in the study. The prevalence of perception of abuse was 40.6%. The most common type of abuse was psychological (98%) and unjustified critique (10.9%), ridiculing (10.7%), shouting (10%), and discredit (9.5%)